Z badań nad inteligencją Łodzi przełomu XIX i XX wieku - Jurek, Lidia (Acta Universitatis Lodziensis. Folia Historica, 2008)
The development of Łódź had been a unique phenomenon in Polish lands. The main reason for this was the distinctiveness of the growth of the city and its social structure. Unlike other Polish urban centres, such as Kraków, Lwów or Warsaw, Łódź emerged as a modern industrial metropolis only in the second half of the nineteenth century. The city’s industrial trait had a very strong influence on its inhabitants, the straight majority of whom, were mostly physical workers, who were growing in number as fast as the fortunes of the factories’ owners did. What is more, the multiethnic nature of the city contributed to the complexity of social relations within its confines. Given these circumstances, examining the shape, place, tasks and social attitudes of the intelligentsia proves to be highly engrossing. Although there is a broad literature concerning the issue of the 19th century Polish intelligentsia, no extended monograph of this subject matter was published with reference to Łódź so far. The article presents some of the issues which have to be taken into consideration while working on this stratum in tódź. It also implies that as for the social attitude of the local intelligents, there were two common paths to follow: aiming at a private success or working as a philanthropist and social activist. Undoubtedly, the character of the city would have encouraged adopting the former and, at die same lime, forced to agree to the latter.